Upaya Pencegahan Container Yang Tidak Termuat Pada Kapal Oleh PT. Sentra Sinar Baru (Persero) Regional Jawa Tengah - Aan Rubiyanto; Eni Tri Wahyuni (Moneter : Jurnal Ekonomi dan Keuangan, 2023)
The purpose of this paper is to determine the occurrence of the return of containers from the port to PT. Sentra Sinar Baru (Persero) Central Java Region due to not being loaded on the ship, delivery orders issued before confirmation to the depot, damage to containers during loading and unloading at the port and at the depo container yard. The data collection method used by the author is the observation method by making direct observations at PT. Sentra Sinar Baru Semarang Branch, interview method by interviewing several staff at PT. Sentra Sinar Baru Semarang Branch, the method of studying the literature contained in the book as a reference in this writing, as well as the method of documentation carried out by collecting documents deemed relevant to the title. The results of this discussion indicate that the prevention of containers that are not loaded on the ship by PT. Sentra Sinar Baru (Persero) in the Central Java region, reducing the occurrence of delivery orders issued early with effective communication between shipping companies and depots, minimizing damage to containers at the port or at the container yard.